Diffusion Tensor Imaging Studies on Spontaneous Subarachnoid Hemorrhage-Related Brain Injury: A Mini-Review - Cho, Min Kyeong; Jang, Sung Ho (Frontiers in Neurology, 2020)
Accurate diagnosis of the presence and severity of neural injury in patients with subarachnoid hemorrhage (SAH) is important in neurorehabilitation because it is essential for establishing appropriate therapeutic strategies and developing a prognosis. Diffusion tensor imaging has a unique advantage in the identification of microstructural white matter abnormalities which are not usually detectable on conventional brain magnetic resonance imaging. In this mini-review article, twelve diffusion tensor imaging studies on SAH-related brain injury were reviewed. These studies have demonstrated SAH-related brain injuries in various neural tracts or structures including the cingulum, fornix, hippocampus, dorsolateral prefrontal region, corticospinal tract, mamillothalamic tract, corticoreticular pathway, ascending reticular activating system, Papez circuit, optic radiation, and subcortical white matter. We believe that these reviewed studies provide information that would be helpful in science-based neurorehabilitation of patients with SAH. Furthermore, the results of these reviewed studies would also be useful for clarification of the pathophysiological mechanisms associated with SAH-related brain injury. However, considering the large number of neural tracts or neural structures in the brain, more research on SAH-related brain injury in other neural tracts or structures should be encouraged.